INTELLECTUAL MODEL OF ENTERPRISES INNOVATIVE DEVELOPMENT IN THE KNOWLEDGE-BASED ECONOMY PARADIGM - Островська, Галина (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The problem of intellectual support for the innovative development of Ukrainian enterprises in the formation of a knowledge-based economy was studied. Emphasis is placed on the fact that the paradigm of the knowledge economy provides the creation of certain conditions through long-term investments in science, education, innovative systems development, information infrastructure constant modernization, and the creation of a favorable environment for market innovations. Under these conditions, intellectual potential is an integrating indicator of internal sources, opportunities, rational solution means of social, cultural, scientific and technical problems, including valuable knowledge of enterprises. An analytical assessment of Ukrainian enterprises intellectual potential and innovative capacity parameters was carried out. A conclusion was made about the high potential and ineffective use of intellectual resources, which negatively affects the innovative development of entrepreneurship. The results of conceptual modeling are indicated, within the framework of which the author's definition of the category "intellectual support of the enterprise innovative development" essence is given. An algorithm for the functioning of the innovative development intellectual support system was formulated for the effective transfer of knowledge between the interaction participants. The structural aspects of the specified system were determined. Methodological principles were developed that ensure effective functioning and regulation (targeted self-organization) of enterprises innovative development intellectual support system from the standpoint of a synergistic management concept. An enterprises innovative development intellectual support model was formed in two ways: on the macro- and micro-levels, which reveals the subjective composition of its participants and the mechanisms of their interaction. It was substantiated the expediency of intellectual support infrastructure forming based on new forms of the innovative enterprise organization, which contribute to the economy innovation. It was confirmed the position regarding the formation and implementation of educational and scientific institutions "third mission" – scientific research and development commercialization, which leads to the new type of universities appearance – entrepreneurial universities. The proposed conceptual approaches, models and mechanisms of the enterprises innovative development intellectual support system reveal new standards of system participants’ interaction, as well as effective use of intellectual potential and intellectual capital development.